Factors affecting the Integration of Local Traditional Products into Quality Assurance Schemes. - KARAGKIOZI, POLYXENI (Journal of Agricultural Sciences (Belgrade), 2019)
This paper investigates the factors that affect the Prespes Beans ("Fassolia Prespon") farmers to adopt the Protected Geographical Indication (PGI) label for their product. The study was based on primary data collected by means of a questionnaire completed by both PGI certified and non-certified producers. The logit model was used for the indication of factors that affect the producers’ decision to certify or not their product as PGI; descriptive statistics measures were also used for the study of leaders’ social features. The research results showed that the producers’ decision of adopting the Protected Geographical Indication (PGI) certification is significantly linked to membership producer organizations (cooperatives or other groups), the years of agricultural experience, the size of the cultivated land as well as the motives for joining Quality Assurance Schemes.